2011
DOI: 10.1001/archoto.2010.254
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Lateral Neck Ultrasonography as a Long-term Outcome Predictor in Papillary Thyroid Cancer

Abstract: Preoperative US is an excellent outcome predictor for lateral neck disease-free interval and for disease-specific survival in PTC. Sonographically based surgical approach provides excellent long-term regional control and validates current treatment guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…In that study, preoperative ultrasound was found to be an excellent outcome predictor for lateral neck disease-free interval and diseasespecific survival (33).…”
Section: Addendummentioning
confidence: 87%
“…In that study, preoperative ultrasound was found to be an excellent outcome predictor for lateral neck disease-free interval and diseasespecific survival (33).…”
Section: Addendummentioning
confidence: 87%
“…If the enlargement of lymph nodes implied by preoperative B-ultrasonic, the lymph node metastasis rate increase to 21% and 6.9% respectively, however without lymph node exploration and enlargement by B-ultrasonic, the rate were2.6% and 0%. Moreno et al (2011) found that preoperative B-ultrasound can predict PTC's tumor-free interval at lateral neck and the tumor-free survival. Shen et al (2010) reported the central lymph node dissection after initial or recurrent tumor, except for a higher temporary hypocalcemia of initial dissection, both of their post-operative complications are similar.…”
Section: Discussionmentioning
confidence: 91%
“…There was no case of death due to the disease. (9)(10)(11)(12)(13)(14), the presence of more than 5 positive LN (11,(15)(16)(17)(18), metastases ≥ 3 cm (11,16,19), and extranodal extension (15,16,(18)(19)(20)(21) are also associated with a poor prognosis (4,5,7,22). In these cases, there is little controversy about the need for a more aggressive initial approach.…”
Section: Evolution Of Patients With Persistent Disease or Tumor Recurmentioning
confidence: 99%
“…In fact, extranodal invasion was observed in only 7/466 patients with LNM < 3 cm and up to 5 positive LN in a previous series (16) and in only 1/87 patients with negative US and up to 5 positive LN in the present study (data not shown). A possible poor prognosis related to the location of LNM in the lateral compartments (N1b) also seems to be minimized when US is negative (9)(10)(11)(12). Finally, the efficacy of initial LN dissection, based on the persistence or not of LNM after surgery (39), is an important prognostic factor.…”
Section: Evolution Of Patients With Persistent Disease or Tumor Recurmentioning
confidence: 99%
See 1 more Smart Citation